Severe chronic diarrhoea secondary to primary lymph node gastrinoma - Abu Ghanimeh, Mouhanna (BMJ Case Rep, 2017)
The existence of primary lymph node (LN) gastrinoma is questionable and controversial. In fact, the presence of gastrinoma in such uncommon site raises the possibility of metastasis from another occult primary site. An extensive evaluation and careful follow-up is always warranted. A female aged 48 years presented with chronic abdominal pain and watery diarrhoea. Her serum gastrin and chromogranin were elevated, and an underlying gastrinoma was suspected. Further evaluation with an octreotide scan, an endoscopic ultrasound and a secretin stimulation test confirmed the diagnosis. Further evaluation for multiple endocrine neoplasia-1 syndrome was negative. She underwent a surgical enucleation near the head of the pancreas. No other lesions were found after careful exploration of the gastrinoma triangle. Histology showed a LN with a neuroendocrine tumour that tested positively with gastrin and chromogranin stains. Her symptoms resolved postoperatively, her serum gastrin normalised and a repeated octreotide scan was negative.